Distal posterior femorotibial artery bypass - Abó, Juan Carlos; Filgueira, José L; Gateño, Nisso (Cirugía del Uruguay, 1972)
The case material includes 4 patients with occlusive lesions in the popliteal artery and arterial trunks of the lower limbs in their proximal sectors. By-pass of distal posterior femoro-tibial artery with saphena magna, was performed. In two patients distal sapheno-tibial distal anastomosis was located midway along the leg, and in the case of the other two, near the ankle. The. authors insist on the ímportance of femoral arteriography, with sufficiently slow focussing to permit visualization of arterial vessels in the leg in their distal segments. Distal anastomosis of posterior fomero-tibial by-pass is preferently located in the upper part of the heelbone sulcus, where the artery is easy to approach and is situated in a superficial position. In three patients the by-pass is still permeable. after 26, 24 and 14 months.